2022
DOI: 10.3389/fphar.2021.820446
|View full text |Cite
|
Sign up to set email alerts
|

A FAK Inhibitor Boosts Anti-PD1 Immunotherapy in a Hepatocellular Carcinoma Mouse Model

Abstract: Anti-PD-1/PD-L1 immunotherapy has limited efficacy in hepatocellular carcinoma (HCC) and does not benefit all patients. A FAK inhibitor (VS-4718) has been reported to improve the microenvironment in some tumors. This study aimed to investigate the effect of the combination of the FAK inhibitor VS4718 and anti-PD1 for the treatment of HCC in a mouse model and its possible mechanism of action. The expression of FAK and infiltrated immune cells in human HCC from the data of TCGA were analyzed. A primary murine HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…PRL‐3 is significantly overexpressed and contributes to HCC malignant behaviors via the FAK signaling pathway 34 . FAK inhibitor was shown to promote PD‐L1 expression and boost anti‐PD1 immunotherapy in an HCC mouse model 35 . In our study, FAK was shown to mediate PTK7‐regulated MMP7 expression and subsequent HCC cell migration and invasion abilities, and provide the insight into FAK plays a critical role in PTK7‐mediated HCC development.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…PRL‐3 is significantly overexpressed and contributes to HCC malignant behaviors via the FAK signaling pathway 34 . FAK inhibitor was shown to promote PD‐L1 expression and boost anti‐PD1 immunotherapy in an HCC mouse model 35 . In our study, FAK was shown to mediate PTK7‐regulated MMP7 expression and subsequent HCC cell migration and invasion abilities, and provide the insight into FAK plays a critical role in PTK7‐mediated HCC development.…”
Section: Discussionmentioning
confidence: 50%
“…34 FAK inhibitor was shown to promote PD-L1 expression and boost anti-PD1 immunotherapy in an HCC mouse model. 35 In our study, FAK was shown to mediate PTK7-regulated MMP7 expression and subsequent HCC cell migration and invasion abilities, and provide the insight into FAK plays a critical role in PTK7-mediated HCC development. Overall, our results suggest that PTK7 plays an essential role in HCC metastasis progression via targeting the FAK-MMP7 pathways.…”
Section: Discussionmentioning
confidence: 51%
“…Simultaneously, it facilitated T cell infiltration leading to an enhancement in the therapeutic outcomes of immune-based interventions for pancreatic cancer ( Blair et al, 2022 ). Combining the FAK inhibitors with anti-PD-1antibodies demonstrated enhanced anti-cancer effects in C57BL/6 J primary hepatocellular carcinoma model with complete immune function, reducing Tregs and TAMs while increasing CD8 + T cell population ( Wei et al, 2021 ). FAK also impedes antigen the processing and presentation in pancreatic cancer, contributing to immune evasion of pancreatic cancer.…”
Section: Role Of Fak In Tmementioning
confidence: 99%
“…FAK stands out as a key player in cancer pathogenesis, being abnormally activated across various cancer types. Its expression level not only is inversely linked to patient survival but also positions FAK as a pivotal target for thwarting tumor progression and curbing recurrence ( Zeng et al, 2016 ; Kanteti et al, 2018 ; Aboubakar et al, 2019a ; Aboubakar et al, 2019b ; Qiao et al, 2020 ; Wei et al, 2021 ; Roy-Luzarraga et al, 2022 ). Rigorous meta-analyses underscore the significance of heightened FAK expression in predicting unfavorable overall survival (OS) outcomes in a spectrum of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the FAK inhibitor VS4718 with anti-PD1 therapy in hepatocellular carcinoma resulted in decreased macrophage numbers and increased CD8+ T-cell numbers [ 141 ]. Additionally, when FAK inhibitors were combined with agents that induce T-cell costimulatory pathways in skin squamous cell carcinoma, the tumors became more sensitive to FAK inhibitors, and this effect was mediated by CD80.…”
Section: Targeting Fak In Combination Therapiesmentioning
confidence: 99%